Typification of the names Santolina ericoides and S. villosa (Asteraceae) revisited - Ferrer-Gallego, P. Pablo; Sáez, Llorenç; Wajer, Jacek; Giacò, Antonio; Peruzzi, Lorenzo (Phytotaxa, 2021)
The typification of the species names Santolina ericoides and S. villosa (Asteraceae) are revisited. The name Santolina ericoides has been applied to plants distributed in the Iberian Peninsula and S France, and the name S. villosa has been applied to a taxon endemic to Spain. These species names have recently been neotypified from specimens kept at the herbarium of the Muséum national d’Histoire naturelle de Paris at P, and at the herbarium PAL (PAL-Gr), respectively. These two type designations are briefly discussed and superseded here because these neotypifications were unnecessary being contrary to Art. 9.8 of the International Code of Nomenclature for algae, fungi, and plants (Shenzhen Code). In this work, all relevant sources, specimens, illustrations, and references cited in the protologues are carefully evaluated for the purpose to fix the application of the names. We have chosen and designated the best admissible lectotype for these two names from the original material.